Characteristics of fly ash geopolymer based on alkaline ratio of activators for building materials: A review - I Dewa Made Alit Karyawan; Ratna Yuniarti; Hasyim Hasyim; Desi Widianty (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
The geopolymer introduced by Davidovits is a new binder for making concrete as an alternative to ordinary Portland cement. One of the materials used to make geopolymers is fly ash. The annual worldwide production of fly ash is estimated to be around 500 Mt. In making geopolymers with fly ash, scientists usually use activators such as silicate and aluminate solutions, as well as with kaolinite. The geopolymerization process is related to the metal oxide ratio of the activator solution. Geopolymers can withstand temperatures up to about 600°C, so they are fire/heat resistant. This paper describes the role of the comparison of dominant elements in a mixture of geopolymer paste with fly ash and alkali which produces the best quality based on compressive strength, where there is an effect of the ratio of alkali on the compressive strength of geopolymer paste. Almost all of the highest compressive strength obtained did not follow the Davidovits rule. This is caused by other factors that affect the compressive strength such as the content of elements such as Si and Al in fly ash and the curing temperature. However, the volumetric and mechanical properties of the artificial aggregate (geopolymer fly ash application) meet the requirements as a road material. It's just that the absorption value is above the requirements (>3%). Seeing the properties of these geopolymers, there is hope to be developed into materials for building materials. Geopolimer yang diperkenalkan oleh Davidovits adalah pengikat baru untuk membuat beton sebagai alternatif pengganti semen Portland biasa. Salah satu bahan yang digunakan untuk membuat geopolimer adalah fly ash. Produksi tahunan fly ash seluruh dunia diperkirakan sekitar 500 Mt. Dalam membuat Geopolimer dari fly ash para ilmuwan biasanya menggunakan aktivator seperti larutan silikat dan aluminat, serta dari kaolinit. Proses geopolimerisasi berkaitan dengan rasio oksida logam dari larutan aktivator. Geopolimer dapat menahan suhu hingga sekitar 600°C, sehingga tahan api/panas. Makalah ini menjelaskan tentang peranan perbandingan unsur-unsur dominan pada campuran pasta geopolimer dengan fly ash dan alkali yang menghasilkan kualitas terbaik berdasarkan kuat tekan, dimana terdapat pengaruh perbandingan alkali terhadap kuat tekan pasta geopolimer. Hampir seluruh kuat tekan tertinggi yang didapatkan tidak mengikuti aturan Davidovits. Hal ini disebabkan oleh faktor lain yang mempengaruhi kuat tekan seperti kandungan unsur-unsur seperti Si dan Al dalam fly ash dan temperatur curing. Namun, properties volumetric dan mekanik agregat buatan (aplikasi geopolymer fly ash) memenuhi persayaratan sebagai bahan jalan. Hanya saja nilai penyerapannya di atas persyaratan (>3%). Melihat sifat-sifat geopolimer tersebut, membuka harapan untuk dikembangkan menjadi material untuk bahan bangunan.